Outcome of Conventional Adipose Tissue Grafting for Contour Deformities of Face and Role of Ex Vivo Expanded Adipose Tissue-Derived Stem Cells in Treatment of Such Deformities. Issue 5 (July 2018) - Bashir, Muhammad Mustehsan; Sohail, Muhammad; Bashir, Afzaal; Khan, Farid Ahmad; Jan, Sadia Nosheen; Imran, Muhammad; Ahmad, Fridoon Jawad; Choudhery, Mahmood S.
Abstract : Objectives: To evaluate the outcomes of conventional fat grafting for facial contour deformities and to describe clinical outcome of a patient with contour deformity of face treated with ex vivo expanded adipose tissue-derived mesenchymal stem cells (ASCs) enriched fat graft. Place and Duration of Study: The Department of Plastic Surgery and Tissue Engineering and Regenerative Medicine Laboratory, King Edward Medical University/Mayo Hospital, Lahore, from September 2015 to September 2017. Methods: Patients with contour deformities of face requiring soft tissue augmentation were included. Fat was harvested, processed, and injected following a standard protocol. Both subjective and objective assessments were performed and complications were also noted. Results: Twenty-five patients underwent 51 fat-grafting sessions over a period of 24 months. Eighteen (72%) patients underwent multiple fat-grafting sessions. Mean (standard deviation) soft tissue thickness after 72 hours and 6 months of first fat graft session was 18.62 (7.2) and 12.88 (6.21) mm, respectively, which corresponds to 30.77 (13)% reduction of transplanted fat. Physician and patient assessment scores were 3.42 (0.92) and 4 (1.04), respectively. Few minor complications were observed. In the patient undergoing ex vivo expanded ASCs enriched fat graft, there was minimal decrease in soft tissue thickness of treated area (44 mm vs 42 mm) 6 months postoperatively and patient was highly satisfied with the outcome after the single session. Conclusion: Conventional fat grafting is safe for correction of facial contour deformities. However, procedure needs to be repeated multiple times to produce satisfactory results. Beneficial effects of ex vivo expanded ASCs enriched fat grafting have a potential to alter the current treatment paradigm of fat grafting for soft tissue reconstruction.